Effects of teriparatide versus alendronate for treatment of postmenopausal osteoporosis: A meta-analysis of randomized controlled trials. Issue 21 (May 2017) - Wang, Ya-Kang; Qin, Si-Qing; Ma, Tao; Song, Wei; Jiang, Ren-Qi; Guo, Jian-Bin; Li, Kun; Zhang, Yu-Min
Abstract: Objectives: Osteoporosis remains a clinical challenge. Teriparatide is an anabolic drug and alendronate is an antiresorptive agent; both are used in the treatment of osteoporosis. Comprehensive reviews investigating the comparative safety and efficacy of teriparatide versus alendronate are scarce. Therefore, we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the safety and efficacy of teriparatide versus alendronate for the treatment of postmenopausal osteoporosis. Methods: We conducted a comprehensive literature review of the PubMed, EMBASE, Cochrane Controlled Trials Registry, and the China Academic Journal Network Publishing databases for relevant RCTs of teriparatide versus alendronate in postmenopausal osteoporosis patients. Outcome measures were percentage change in lumbar spine and femoral neck bone mineral density (BMD) and incidence of vertebral and nonvertebral fractures. Effect size was reported as weighted mean differences (WMDs) for continuous outcomes and odds ratios (OR) for dichotomous outcomes, with associated 95% confidence intervals (CIs). Results: Six trials involving 618 patients were included. The meta-analysis demonstrated a significant increase in lumbar spine BMD (WMD: 3.46, 95% CI: 2.15–4.77, P < .00001), but not femoral neck BMD (WMD = 1.50, 95% CI: 0.04–2.95, P = .04), in postmenopausal osteoporosis patients treated with teriparatide compared with alendronate for 6 to 18 months. These beneficial effects were apparent in the lumbar spine at 12 months of treatment (WMD: 4.49, 95% CI: 2.57–6.40, P < .01). Teriparatide was not superior to alendronate in reducing fracture risk (OR: −0.03, 95% CI: −0.12 to 0.07; P = .52). Conclusion: Teriparatide may be superior to alendronate for increasing lumbar spine BMD in postmenopausal osteoporosis. The efficacy and safety of long-term teriparatide and alendronate treatment in postmenopausal osteoporosis should be further investigated in clinical trials.